Unsatisfactory quality of E. coli asparaginase biogenerics in India: Implications for clinical outcomes in acute lymphoblastic leukaemia. Issue 11 (3rd May 2021) - Sidhu, Jasmeet; Gogoi, Manash Pratim; Agarwal, Praveen; Mukherjee, Tathagata; Saha, Debparna; Bose, Priyanka; Roy, Prakriti; Phadke, Yogesh; Sonawane, Bhatu; Paul, Pritha; Saha, Vaskar; Krishnan, Shekhar
Abstract: Background: The biotherapeutic asparaginase is a cornerstone of therapy in acute lymphoblastic leukaemia (ALL). With limited access to the original native Escherichia coli ‐derived asparaginase (EcASNase), a variety of EcASNase biogenerics are used in low‐middle‐income countries (LMICs). The variable quality of these biogenerics potentially influences clinical outcomes. Procedure: Seven biogeneric EcASNases (P1–P7) marketed widely in India were evaluated, with P2 as an exemplar for in vivo monitoring. Therapeutic activity of P2 (10, 000 IU/m 2 /dose, intramuscular, every 72 hours) was monitored during induction therapy, and drug‐related toxicities recorded. Molecular identity, purity and in vitro drug activity of seven biogenerics were characterised using multimodal analyses, and findings compared with reference EcASNase (R). Results: In patients ( N  = 62) receiving P2, subtherapeutic asparaginase activity (<100 U/L) was observed in 66% (46/70) of trough timepoints (72 hours postdose) during induction. Twelve patients (19%), 11 with high‐risk ALL, developed hypersensitivity. Isoforms of EcASNase were identified in all seven biogenerics. All generic products contained impurities with batch‐to‐batch variability. These included high levels of protein aggregates and host cell protein contamination. In vitro assays of EcASNase activity and leukaemia cell line cytotoxicity were not discriminatory. Conclusions: Our findings confirm widespread concerns over the unsatisfactory quality and therapeutic activity of native EcASNase biogenerics marketed in LMICs. Appropriate use of these products requires monitored studies to identify clinical suitability and determine appropriate dosing and schedule. For large parts of the world, assured access to high‐quality asparaginases remains an unmet therapeutic need.